Penerapan Berkumur Menggunakan Larutan Madu untuk Mengatasi Masalah Keperawatan Kerusakan Membran Mukosa Oral pada Pasien Kanker Payudara - Dewi Damayanti (LPPM Sikes Panca Bhakti Bandar Lampung, 2019)
One of the side effects of chemotherapy is mucositis. Mucositis is an inflammation and ulceration of the mucous wall in the mouth of clients who receive cancer therapy. Mukositis causes patients to experience pain, decreased appetite and delay in chemotherapy. The aim of this study was to analyze the effect of applying gargling on a low solution in reducing mucositis in cancer patients due to chemotherapy. The method in this study is applied research with One-Group Pretest-Postest Design. The sample selection technique in this study use non probability sampling with purposive approach. This study used the Oral Assessment Guide (OAG) research instrument to assess mucositis scores. This study showed that gargling of honey solution can decrease the mucositis score in both respondents. The results of gargling honey solution can be used as one application to overcome mukositis in breast cancer patients who underwent chemotherapy at RSAM Lampung Province. The recommendation for next researcher to conduct more sample size and the presence of control groups and groups who were given intervention to obtain statistical results and more valid.